Causal Structure of Toll Road Tariff Determination in Public Private Partnership Projects: A System Dynamics Approach - Anggito Adji Wicaksono; Farida Rachmawati (Journal La Multiapp, 2026)
The Solo Yogyakarta Yogyakarta International Airport Toll Road is a national strategic infrastructure project in Indonesia developed under a public private cooperation scheme using a build operate transfer arrangement. In this scheme, toll tariffs function as the primary mechanism for investment recovery, making tariff determination a critical factor influencing traffic demand and project feasibility. This study aims to develop a system dynamics based model to explain the structural relationships governing toll tariff determination in toll road projects implemented through public private cooperation. The research applies a quantitative modeling approach using system dynamics, following stages of problem formulation, development of a dynamic hypothesis, and construction of a causal loop diagram. Key variables are identified through literature review, expert judgment, and secondary data analysis, including toll tariffs, average daily traffic, user affordability, operational costs, and financial performance indicators. The analysis focuses on identifying cause effect relationships and feedback structures that influence traffic demand and revenue behavior. The results show that toll tariff determination is governed by interacting reinforcing and balancing feedback loops, with traffic volume emerging as a central variable linking tariff policies to revenue and financial performance. Higher tariff levels may increase unit revenue while simultaneously reducing traffic demand due to affordability constraints, whereas economic growth and service improvements support reinforcing demand effects. This study concludes that toll tariff determination should consider dynamic interactions among demand, affordability, and financial variables rather than relying solely on static cost-based approaches.